Role models-implementation-based approaches to using roles - Selcuk, Yunus Emre; Erdogan, Nadia (WILEY, 2011)
A role of an entity can be defined as the set of properties that are important for an object in order to behave in a certain way, as expected by a set of other objects. A role model is a software that specifies a style of designing and implementing roles. This paper evaluates roles in the context of modeling dynamic systems by examining its foundations, surveying the recent role models available for academic use and giving implementation examples. Copyright (C) 2010 John Wiley & Sons, Ltd.
Keywords: role models; instance-level specialization; object-level inheritance; OBJECTS; Computer Science